Molecular cloning of unintegrated and a portion of integrated moloney murine leukemia viral DNA in bacteriophage lambda. - Berns, A J (1980)
A covalently closed circular form of unintegrated viral DNA obtained from NIH 3T3 cells freshly infected with Moloney murine leukemia virus (M-MLV) and a port of the endogenous M-MLV from the BALB/Mo mouse strain have been cloned in bacteriophage lambda. The unintegrated viral DNA was cleaved with restriction endonuclease HindIII and inserted into the single HindIII site of lambda phage Charon 21A. Similarly high-molecular-weight DNA from BALB/Mo mice ws cleaved sequentially with restriction endonucleases EcoRI and HindIII and separated on the basis of size, and one of the two fractions which reacted with an M-MLV-specific complementary DNA was inserted into the HindIII site of Charon 21A. Recombinant clones containing M-MLV-reacting DNA were analyzed by restriction endonuclease mapping, heteroduplexing, and infectivity assays. The restriction endonuclease map of the insert derived from unintegrated viral DNA, lambda x MLV-1, was comparable to published maps. Electron microscope analysis of the hybrid formed between lambda x MLV-1 DNA and 35S genomic M-MLV RNA showed a duplex structure. The molecularly cloned lambda x MLV-1 DNA contained only one copy of the long terminal repeat and was not infectious even after end-to-end ligation of the insert DNA. The insert DNA derived from endogenous M-MLV, lambda x MLVint-1, contained a DNA stretch measuring 5.4 kilobase pairs in length, corresponding to the 5' part of the genomic viral RNA, and cellular mouse DNA sequences measuring 3.5 kilobase pairs in length. The viral part of the insert showed the typical restriction pattern of M-MLV DNA except that a single restriction site, PvuII, in the 5' long terminal repeat was missing. Reconstructed genomes containing the 5' half derived from the integrated viral DNA and the 3' half derived from the unintegrated viral DNA were able to induce XC plaques after transfection in uninfected mouse fibroblasts.